ANALISIS PENILAIAN KINERJA KEUNGAN DENGAN MENGGUNAKAN RASIO PROFITABILITAS, ECONOMIC VALUE ADDED (EVA), DAN COMMON SIZE PADA PT. PELABUHAN INDONESIA SUB REGION JAWA REGIONAL 3 PROBOLINGGO - Refianty, Refida; Amani, Tatik; Vidiyastutik, Elok Dwi (Relawan Jurnal Indonesia, 2024)
This research aims to analyze Financial Performance Assessment Using Profitability Ratios, Economic Value Added (EVA), and Common Size in terms of the financial position report and profit and loss report for 2020-2022. The data used is secondary data in the form of reports of financial position and profit and loss for 2020-2022. The data analysis method used is quantitative descriptive. The results of this research are about Financial Performance Assessment Analysis at PT. Pelabuhan Indonesia (Persero) Sub Region Java Regional 3 Probolinggo which shows that in 2020-2022 the company was able to achieve the ROE standard, namely ROE > 40% for the last 3 years. Based on EVA analysis, it shows that 2020-2021 has a positive value (EVA > 0) and 2022 has a negative value (EVA < 0). Based on the Common Size analysis, business profit/loss has increased in the last 3 years and the company is able to generate profits based on income levels that are getting better every year.